2019
DOI: 10.1002/chem.201900700
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework (MOF)‐Derived Carbon‐Mediated Interfacial Reaction for the Synthesis of CeO2−MnO2 Catalysts

Abstract: CeO2‐based catalysts are widely studied in catalysis fields. Developing one novel synthetic approach to increase the intimate contact between CeO2 and secondary species is of particular importance for enhancing catalytic activities. Herein, an interfacial reaction between metal–organic framework (MOF)‐derived carbon and KMnO4 to synthesize CeO2−MnO2, in which carbon is derived from the pyrolysis of Ce‐MOFs under an inert atmosphere, is described. The MOF‐derived carbon is found to restrain the growth of CeO2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…In comparison with sample CoFe 2 O 4 (723 K) at 781.02 eV, the shift of corresponding peak of CoFe 2 O 4 /C (623 K) to 781.89 eV implies the strong interaction between CoFe 2 O 4 and porous carbon (Figure 6b). 45 As shown in Figure 6c and Figure S7c (Supporting Information), the spectra of O 1s for all the samples are resolved into three peaks and contributed to O Fe/Co (lattice oxygen), O OH (surface oxygen), and O V (oxygen vacancies) 46. Table S2 (Supporting Information) shows the area percentages of different O elemental calculated from XPS spectra.…”
Section: Resultsmentioning
confidence: 97%
“…In comparison with sample CoFe 2 O 4 (723 K) at 781.02 eV, the shift of corresponding peak of CoFe 2 O 4 /C (623 K) to 781.89 eV implies the strong interaction between CoFe 2 O 4 and porous carbon (Figure 6b). 45 As shown in Figure 6c and Figure S7c (Supporting Information), the spectra of O 1s for all the samples are resolved into three peaks and contributed to O Fe/Co (lattice oxygen), O OH (surface oxygen), and O V (oxygen vacancies) 46. Table S2 (Supporting Information) shows the area percentages of different O elemental calculated from XPS spectra.…”
Section: Resultsmentioning
confidence: 97%
“…For example, some catalysts derived from Cebased MOFs can be used in CO oxidation. [97,[99][100][101][102][103][104] Zhang et al reported cauliflower-and strawsheave-like Ce-based catalysts derived from MOF materials with large surface areas. These porous catalysts can provide enough active sites and oxygen vacancies and exhibit excellent catalytic performance for CO oxidation.…”
Section: Harmful Gas Conversionmentioning
confidence: 99%
“…For the O1s, the peak of O latt distributed at ≈528-530 eV, the small shift was attributed to the difference of the CeO and CoO bonds; the peak of O ads was located at ≈532.9 eV which was attributed to the hydroxyl species of water adsorbed on surface; [63][64][65] simultaneously, the peak located at 531.3 eV can be assigned to the O vac which referred to the defect site with low oxygen coordination. [66,67] With the introduction of the Co, the content of O vac posed a trend of S3, Supporting Information). As for the Co 2p, the deconvoluted peaks of 779.5 and 794.6 eV were assigned to Co 3+ , and the peaks of 794.5 and 781.1 eV were ascribed to Co 2+ , and the two peaks at 803.6 and 785.5 eV were assigned to the weak 2p satellite peaks.…”
Section: Assembly and Characterizationsmentioning
confidence: 99%